3D Multiscale Integrated Modeling Approach of Complex Rock Mass Structures. (10th July 2014) - Li, Mingchao; Han, Yanqing; Wang, Gang; Yan, Fugen
Abstract : Based on abundant geological data of different regions and different scales in hydraulic engineering, a new approach of 3D engineering-scale and statistical-scale integrated modeling was put forward, considering the complex relationships among geological structures and discontinuities and hydraulic structures. For engineering-scale geological structures, the 3D rock mass model of the study region was built by the exact match modeling method and the reliability analysis technique. For statistical-scale jointed rock mass, the random network simulation modeling method was realized, including Baecher structure plane model, Monte Carlo simulation, and dynamic check of random discontinuities, and the corresponding software program was developed. Finally, the refined model was reconstructed integrating with the engineering-scale model of rock structures, the statistical-scale model of discontinuities network, and the hydraulic structures model. It has been applied to the practical hydraulic project and offers the model basis for the analysis of hydraulic rock mass structures.